Development and pilot testing of a clinical guideline for the comprehensive management of pain in an adult intensive care unit in Ghana: an intervention study - Ofori, Bridget Senanu (My University, 2017)
The purpose of the study was to develop and pilot test a clinical guideline for the comprehensive management of acute pain in the adult Cardiothoracic Intensive Care Unit (CT-ICU) in Ghana. The intervention study employed both qualitative and quantitative designs using the pre-and post-intervention method. The objectives of the study were to develop and pilot test a clinical guideline for the comprehensive management of acute pain in adult patients admitted to the CT-ICU post cardiothoracic surgery. The site for the study was a six-bedded cardiothoracic Intensive Care Unit (ICU) of an academic hospital in the Greater Accra region of Ghana. The intervention was assessed in terms of a primary outcome of patients’ comfort and secondary outcomes of patients’ satisfaction with pain management, length of stay in the CT-ICU and cost of CT-ICU care. To meet the objectives of the study, it was conducted in three (3) phases: Phase 1 - Exploratory phase, Phase 2 - Development and validation phase and Phase 3 – Pilot testing phase. In Phase 1 of the study, a systematic review of literature was undertaken to identify methods that would ensure effective pain management in adult Intensive Care Units. CT-ICU nurse experts (n=12) and CT-ICU doctors’ (n=8), patients who were treated in the CT-ICU (n=3) and their relatives (n=3) were interviewed using focus groups and individual interviews to identify their views and opinions on pain and its management in the CT-ICU and measures to improve pain management. In Phase 2, a draft clinical guideline for the comprehensive management of pain in the CT-ICU was developed based on the findings from the exploratory phase (Phase 1). The guideline was presented to CT-ICU nurse experts and doctors, patients who received treatment in the CT- ICU and their relatives for validation. In Phase 3, the clinical guideline was piloted and outcomes assessed. Baseline assessments of patients (n=65) comfort and satisfaction with pain management in the CT-ICU was conducted and patients (n=65) length of stay and cost of patients (n=65) CT-ICU treatment was assessed before implementing the guideline (pre- test). Outcomes were then assessed by repeating the tests with the same sample size (n=65) for each assessment after the intervention (post-test). A comparison was then undertaken between the pre-and post-test to determine the effect of the intervention. The systematic review of literature was analysed using the narrative approach and qualitative data using the six steps of qualitative analysis by Creswell (2014). Statistical tests employed in the study included the Fisher’s Exact and two-sample t-tests. Testing was done on the 0.05 (p<0.05) level of significance. The statistical software package STATA© version 14 was used to analyse the data. The comparison of pre-and post-tests indicated that the intervention significantly reduced patients’ pain scores (p=0.000), increased satisfaction with nurses’ administration of analgesia (p=0.001), increased satisfaction with nurses’ responsiveness to patients’ complaints of pain (p=0.000) increased satisfaction with pre-operative education on post- operative pain (p=0.001) and reduced cost of CT-ICU care (p=0.001). The intervention improved pain management in the CT-ICU and it is recommended that pain be given the priority that it deserves to improve ICU patients’ outcomes.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy, 2017.
Keywords: Thoracic surgery; Pain -therapy; Critical Care - methods; Respiratory Tract Diseases-rehabilitation